A study of metabolism of para-nitrophenol in Arthrobacter sp. SPG - Akash Mukul Jyothi (African Journal of Environmental Economics and Management, 2015)
Arthrobacter sp. SPG utilized p-nitrophenol (pNP) as the sole carbon, nitrogen, and energy source. The stoichiometric amounts of nitrite ions were released from pNP. The pathway of pNP degradation was studied for strain SPG. On the basis of thin layer chromatography, high performance liquid chromatography and gas chromatography-mass spectrometry, hydroquinone (HQ) was identified as major intermediate product. HQ dioxygenase activity was found in crude extract of pNP induced cells of strain SPG that suggested the cleavage of HQ into gamma-hydroxymuconic semialdehyde. This study clearly showed that strain SPG degraded pNP via HQ pathway. Arthrobacter sp. SPG degrades various nitroaromatic compounds including pNP, 2-chloro-4-nitrophenol, 3-methyl-4-nitrophenol, 2-nitrocatechol and 2-nitrobenzoate. This strain would be a suitable candidate for bioremediation of nitroaromatic compounds contaminated sites.